Digitalisation in India: The class agenda - Dreze, Jean; Research Unit for political economy (India Three Essays Collective, 2025)
Bill Gates, Nandan Nilekani, the IMF, the World Bank, and the World Economic Forum are all agreed: India$1 (Bs digitalisation process is transformational. Digitalisation saves the Indian government money, ensures the poor get their payments, enables healthcare, spreads education, empowers the once-excluded, raises productivity and turbo-charges consumption. Indeed it sets a blueprint for other countries to follow. The authors of this collection of essays eschew such magical thinking and look at the actual process of digitalisation in India: its effects on growth, employment, welfare, healthcare, education, urban planning, financial services and agriculture. s